Impacto dos derivativos na base de cálculo do imposto sobre a renda - Sanson, Carla Campos Moreira (2011)
This study examines the impact of derivative transactions on the income tax calculation basis. The analysis starts by defining the concept of income, defending its constitutional provision. After determining the concept of income, the next step was to study the tax matrix rule, especially the calculation basis, emphasizing the importance of Accounting for its determination. In the sequence there is the examination of derivative instruments, and the discussion of their economic and legal nature, in addition to the analysis of the main uses/strategies of those instruments. Upon the exploration of all elements, it was possible to analyze the use of derivatives and their main impacts on the income tax calculation basis, which enabled the discussion of how such instruments are considered in the appraisal of taxable income and how they should affect the income tax calculation basis to reflect the strategy adopted by the legal entity and result in the effective taxation of income, in line with its concept defended in this work